Prevalence of betel nut chewing and its pattern of distribution across the Bangladeshi socio-demographics - Abrar Wahab; Koustuv Dalal; Minhazul Abedin; Shagoofa Rakhshanda; Farah Naz Rahman; A. K. M. Fazlur Rahman; Aminur Rahman; Saidur Rahman Mashreky (Scientific Reports)
Abstract In Bangladesh, chewing betel nut has become culturally and socially approved, becoming a mounting public health concern. This study aimed to estimate the current prevalence of betel nut chewing, identify the sociodemographic correlates in urban and rural settings, and identify any vulnerable group for future policy-making to address this problem. This is a retrospective study of secondary data analysis based on the data of the Bangladesh Health and Injury Survey 2016. The outcome variable of interest was the self-reported practice of chewing betel nuts. Only ≥ 18 years old participants were considered. In the logistic regression model, the odds ratios with 95% confidence intervals were used to determine the correlates of each independent variable. The multivariable model’s explanatory variables were all tested to ensure no multi-collinearity in the final model. The prevalence of betel nut chewing was 31.4% among the study population. Multivariate analysis showed that participants aged 65 years and above were 10 times more likely to be betel nut users (AOR 10.17; 95% CI 9.58–10.79), while rural populations were 1.24 times more likely to use betel nut (AOR 1.24; 95% CI 1.21–1.27). Given the significant public health burden, targeted interventions are warranted to mitigate its impact. The findings indicate that betel nut chewing is highly prevalent, particularly among older, illiterate, and rural populations, demonstrating stark social and geographic inequalities. However, as the data were collected in 2016, the current socio-political and economic changes in Bangladesh may have influenced this trend, limiting the direct applicability of the findings to the present context.